2021
DOI: 10.3390/nu13113696
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Anti-Inflammatory Diet Ingredients and Lifestyle Exercise with Inflammaging

Abstract: One of the latest theories on ageing focuses on immune response, and considers the activation of subclinical and chronic inflammation. The study was designed to explain whether anti-inflammatory diet and lifestyle exercise affect an inflammatory profile in the Polish elderly population. Sixty individuals (80.2 ± 7.9 years) were allocated to a low-grade inflammation (LGI n = 33) or high-grade inflammation (HGI n = 27) group, based on C-reactive protein concentration (<3 or ≥3 mg/L) as a conventional marker o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Piezo1 channel provides solid theoretical support for these clinical prevention measures. This also reminds us that for chronic inflammation caused by mechanical damage, a good lifestyle is better than all treatments after inflammation ( 138 , 139 ). However, most chronic tissue inflammation has an insidious onset, and damaging mechanical signals are usually long-standing before clinical symptoms.…”
Section: Pharmacology and Physical Regulation Of Piezo1 Channelmentioning
confidence: 83%
“…Piezo1 channel provides solid theoretical support for these clinical prevention measures. This also reminds us that for chronic inflammation caused by mechanical damage, a good lifestyle is better than all treatments after inflammation ( 138 , 139 ). However, most chronic tissue inflammation has an insidious onset, and damaging mechanical signals are usually long-standing before clinical symptoms.…”
Section: Pharmacology and Physical Regulation Of Piezo1 Channelmentioning
confidence: 83%
“…Most clinical trials and observational studies have used CRP as a biochemical marker of systemic inflammation that is produced following stimulation by various cytokines that can be the drivers of an acute response to trauma, infection, ischemia and other inflammatory conditions such as physical activity. CRP also upregulates the release of pro-inflammatory cytokines and inhibits the release of NO, which could disrupt tissue regeneration [50]. Nonetheless, our study is the first to demonstrate the anti-inflammatory properties of chicken breast extract.…”
Section: Discussionmentioning
confidence: 65%
“…High levels of IL-1β, together with IL-6 and TNFα, are associated with an increased risk of morbidity and mortality in older adults. In particular, cohort studies have indicated that IL-1β, IL-6, and TNFα are involved in the alteration of nutritional status, poor physical performance, loss of muscle strength, cognitive decline, and cardiological, neurological, and vascular events [ 30 , 31 ]. In our study, IL-1β and TNFα have reached particularly high concentrations (14-fold increase) and specificity approx.…”
Section: Discussionmentioning
confidence: 99%
“…The low AUC 0.555 (sensitivity 63.6% and specificity 19.4%) for IL-6 underlines the low diagnostic utility of this cytokine in our study. TNFα was also detected at elevated levels in most studies of older adult populations and was associated with frailty and reduced functional capacity, as well as increased CVD mortality [ 21 , 31 , 34 , 35 ]. TNFα plays a pivotal role in endothelial dysfunction through the disturbance it causes to the equilibrium between endothelial nitric oxide synthase (eNOS) and inducible nitric oxide synthase (iNOS) activities, which results in pro-apoptotic NO activity [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%